Transformation of dynamical practical lab for interactive virtual learning experience - Choon, Lih Hoo (Penerbit Universiti Kebangsaan Malaysia, 2021)
Starting from the year 2020, the pandemic situation has forced a shift of most learning into the online mode. Making it much more challenging to exercise the physical lab work. Various approaches such as lab demo video and live discussion session were introduced as the immediate alternatives. However, these alternative models have a limitation where learners are still disconnected from the actual hardware for the hands-on learning experience. Available virtual lab modules in the market are costly and do not necessarily fit the required learning outcomes of courses. In this research, an initiative was taken to convert an engineering physical lab through commonly used software. The PowerPoint-Lab (PPT-Lab) is a low-cost lab tool that enhances the interface and interactive element in practical activities while engaging multiple learning domains within learners. Using the available functions in PowerPoint, a slide is designed and embedded with the 3D computer-aided design models to allow a virtual touch experience of the experimental hardware which is not possible with the 2D images in the lab manual. The PPT-Lab was implemented across Malaysia and Edinburgh campuses for the ‘Wheel and Axle Acceleration’ experiment. The PPT-Lab enables students to practically run the experiment virtually and collect individual distinct data which preventedplagiarism. The quality of students’ reports is comparable with the reports during physical lab time. A survey with first-timers and experienced students to the physical lab received positive feedback. A high number of students agreed that the PPT-Lab enabled them to run the same lab work off-campus.